Radiographers’ knowledge and attitude toward informed consent - Alshamrani, Khalaf (Acta Bioethica, 2023)
Health professionals are obliged to provide the patient and/or his or her guardian with information about examinations and treatment. In the case of examinations involving the use of ionizing radiation, informed consent is essential to weigh the associated benefits and risks. This study evaluates the knowledge and attitude of radiographers regarding informed consent in the radiology department. It is a descriptive cross-sectional study using an online questionnaire, divided into three sections and containing 19 questions, detailing the demographics, knowledge, and attitude of radiographers. Participant responses were scored between 1 and 3, then calculated and averaged to determine mean scores. Student’s t-test was used to determine the statistical significance between means. Mean scores for knowledge and attitudes ranged from 11.60 ±1.72 to 18.73 ±1.84. Radiographers with more experience showed a statistically significant difference (17.45 ±1.23) (p < 0.00) with those with less experience (15.34 ±1.52). Twenty-one percent of the respondents did not seek consent from patients prior to examination. This study demonstrated that these professionals are knowledgeable about informed consent; however, more emphasis should be placed on practice by providing training courses and disseminating correct practice.